Outcome of Bleb Revision With Autologous Conjunctival Graft Alone or Combined With Donor Scleral Graft for Late-onset Bleb Leakage With Hypotony After Standard Trabeculectomy With Mitomycin C. Issue 2 (February 2021) - Laspas, Panagiotis; Wahl, Jochen; Peters, Henning; Prokosch-Willing, Verena; Chronopoulos, Panagiotis; Grehn, Franz; Pfeiffer, Norbert; Hoffmann, Esther M.
Abstract : Précis: Treatment of leakage with ocular hypotony after trabeculectomy with mitomycin C (MMC) can be safely achieved through conjunctival patch alone or combined with donor scleral graft in cases of melted underlying sclera. Purpose: To report outcomes of 2 surgical approaches for treating ocular hypotony in eyes with blebs with late-onset leakage after standard trabeculectomy with MMC. Methods: Thirty consecutive cases with bleb leakage and hypotony underwent bleb revision surgery between 2009 and 2014 by the same surgeon (J.W.) at the Department of Ophthalmology of the Mainz University Medical Center, Germany. In 18 patients, an autologous conjunctival patch graft was applied. In 12 patients, the underlying sclera was found melted and an additional scleral donor graft was sutured in place. The authors analyzed intraocular pressure, visual acuity, and optical coherence tomography of the macula preoperatively at 1 day, 1 week, 4 weeks, and 6 months after surgery. Results: The mean IOP was 6.2±3.5 mm Hg preoperatively and 21.7±16.4 mm Hg at 1 day, 13.7±6.7 at 1 week, 13.1±5.1 mm Hg at 4 weeks, and 12.1±4.7 mm Hg at 6 months after surgery. Visual acuity (logMar) increased from 0.57±0.49 preoperatively to 0.49±0.40 at 6 months. Optical coherence tomography showed flattening of macular folds that were present before treatment. No serious adverse event was reported. Conclusions: This revision technique with conjunctival patch and/or additional donor scleral graft is an effective and safe method for treating late bleb leakage and hypotony maculopathy after trabeculectomy with MMC.